Assessing the Validity of the Quartile Risk Model of Dissociation for Predicting Deliberate Self-Harm. Issue 5 (20th October 2019) - Dorahy, Martin J.; Carrell, John M; Thompson, Neil
ABSTRACT: Deliberate self-harm (DSH) involves a physical act with the intent of harming the self. There are many precipitants to this behavior, with dissociation receiving increasing attention. The current study examined the quartile risk model for predicting deliberate self-harm, which proposes that four quadrants of dissociation (low normative, high normative, low clinical, and high clinical) represent varying levels of risk for engagement in DSH. The model posits that quadrants one and three (low normative, low clinical), protect against engagement in deliberate self-harm. Quadrants two and four (high normative, high clinical), represent an increased risk of engaging in DSH. The current study also investigated the association between shame and deliberate self-harm. College students ( n = 247) completed measures assessing trait dissociation, state and trait shame, and deliberate self-harm. Results did not support the quartile risk model, rather they suggested a general increasing level of deliberate self-harm with heightened dissociation. Furthermore, trait shame was significantly associated with deliberate self-harm. Significantly more state shame was found to occur before engaging in deliberate self-harm relative to after. Results suggest shame and dissociation are related to increased DSH.